Determination of demographic, epidemiological, and socio-economic determinants and their potential impact on malaria transmission in Mannar and Trincomalee districts of Sri Lanka. (December 2016) - Gunathilaka, Nayana; Abeyewickreme, Wimaladharma; Hapugoda, Menaka; Wickremasinghe, Rajitha
Abstract Background Malaria was an endemic problem in Mannar and Trincomalee districts of Sri Lanka until the recent past. Currently, no local case has been found since October 2012. Therefore, the present study was conducted to identify existing demographic, epidemiological and socio-cultural factors in Mannar and Trincomalee districts of Sri Lanka, since there is limited information available on the potential influence of above variables responsible for low malaria transmission. Methods An analytical cross-sectional survey was carried out on selected demographic, epidemiological and socio-economic variables in 32 localities under eight sentinel sites (Each sentinel with four localities) using a pre-defined questionnaire during June–September 2012. Household heads of 45 houses from each locality were selected randomly to participate in the present study. Data were analysed using the Paired Chi Square test and Bray–Curtis method. Results A total of 1440 household heads were interviewed. Both districts indicated statistically acceptable similarities (p > 0.05) in age structure, gender, family size and presence of animals. The knowledge on malaria was observed under "Poor" category. The protective measures against mosquito bites, spraying status of houses and occupation pattern were varied significantly in both districts (p < 0.05). Educational level was statistically similar (p > 0.05) in both districts. Majority of the families were identified as living in "Moderate" house type under low economic condition. Both populations were indicated 85 % similarity according to Bray–Curtis analysis. Conclusion Lack of awareness in these communities about the disease may facilitate to the re-emerge of malaria.